Pengaruh Pengembangan Karir dan Prestasi Kerja Terhadap Kinerja Karyawan Pada PT Sinar Utama Manufacture Serang - Iskandar, Aldo Kusumah; Sembiring, Edy Suranta Karina (Jurnal ATAMA, 2023)
The purpose of this study was to determine the effect of career development on employee performance, to determine the effect of work performance on employee performance and to determine the effect of career development and career development together on employee performance at Sinar Utama Manufacture Company Serang. This research uses a quantitative approach. As for the population in this study were 43 employees of Sinar Utama Manufacture Company Serang. while the sample with the sample technique was saturated so that the sample taken was entirely from the population with a sample of 43 employees. The results of this study in the first hypothesis have a significant effect between career development on employee performance at Sinar Utama Manufacture Company Serang. in the t test, obtained results tcount> ttable (4.220> 2.017) with a significance level of 0.00 (0.00 <0 , 05) so that the Alternative Hypothesis (Ha) is accepted and the Zero Hypothesis (H0) is rejected. The Second Hypothesis there is a significant influence between work performance on employee performance at Sinar Utama Manufacture Company Serang. in the t test, the results obtained tcount> ttable (2.142> 2.017) with a significance level of 0.04 (0.04 <0.05) so The Alternative Hypothesis (Ha) is accepted and the Zero Hypothesis (H0) is rejected. Third Hypothesis there is an influence between career development and work performance on employee performance at Sinar Utama Manufacture Company Serang. with a decision of Fcount> Ftable (14,394> 3,232) with a significance level of 0.00 (0.00 <0.05) with a significance level of 0.00 (0.00 <0.05) so that the Alternative Hypothesis (Ha) is accepted and the Zero Hypothesis (H0) is rejected.